Identifikasi Entamoeba hystolitica dan Balantidium coli pada Lalat di Pasar Legi Surakarta - Hani Dwi Lestari; Tri Mulyowati (Biomedika, 2019)
Flies is one of the insects belonging to the Diptera Order whose presence can disturb human tranquility and as a mechanical vector of disease transmission. The habit of flies that like dirty places like markets that cause all the body parts of flies can easily carry intestinal protozoa type parasites on the body such as Entamoebahistolytica, Entamoeba coli, Giardia lamblia, and Balatidium coli. Some species of Flies receive considerable attention in health. Diseases that are usually transmitted flies include cholera, diarrhea, dysentery, typhus, and digestive diseases.The research was conducted at Parasitology Laboratory of Faculty of Health Sciences Setia Budi University, Surakarta. The sample used was 40 samples consisting of 20 samples of Muscadomestica and 20 samples of Chrysomyamegachepala. Identification of Entamoeba hystolitica, Balantidium coli in flies was performed by sedimentation method using NaCllauratan 0.9% and then microscopic observation. Based on identification result of Entamoeba hystolitica dan Balantidium coli on flies Muscadomestica and Chrysomya megacephala obtained in Legi Market, Surakarta found 1 Entamoeba histolytica cyst in Muscadomestica with percentage of 5% and 2 Trofozoit Balantidium coli at Chrysomyamegacephala with percentage 10%.